DOP42 Efficacy of etrasimod on symptomatic relief in patients with ulcerative colitis: an analysis of the phase 3 ELEVATE UC 52 and ELEVATE UC 12 trials. (30th January 2023) - Chaparro, M; Armuzzi, A; Irving, P M; Allez, M; Dubinsky, M C; Sands, B E; Goetsch, M; Wang, W; Shan, K; Woolcott, J; Bartolome, L; Wosik, K; et al.
Abstract: Background: Patient-reported outcomes such as stool frequency (SF) and rectal bleeding (RB) are important measures of ulcerative colitis (UC) activity and treatment effect. Etrasimod is an investigational, once-daily, oral, selective sphingosine 1-phosphate receptor 1, 4, 5 (S1P1, 4, 5 ) modulator in development for the treatment of moderately to severely active UC. We evaluated RB and SF subscores to assess symptomatic relief in the ELEVATE UC phase 3 programme. Methods: In ELEVATE UC 52 (NCT03945188) and ELEVATE UC 12 (NCT03996369), patients (16-80 years) with moderately to severely active UC were randomised 2:1 to once-daily etrasimod 2 mg or placebo (PBO). ELEVATE UC 52 utilized a treat-through design comprising a 12-week induction period followed by a 40-week maintenance period. ELEVATE UC 12 comprised a 12-week induction period. A key secondary endpoint was the proportion of patients with symptomatic remission (SF =0 [or =1 with a ≥1-point decrease from baseline] and RB =0) at week 12 and at week 52. RB and SF subscores, achievement of symptomatic remission, complete symptomatic remission (SF =0 and RB =0), and symptomatic response (≥30% decrease from baseline in composite RB/SF subscores) were assessed at each visit. Achievement of symptomatic remission was also summarized by subgroups in patients with prior biologic/Janus kinase inhibitor (bio/JAKi) use (yes [1, >1], no) and baseline corticosteroid use (yes, no). Results: More etrasimod- vs PBO-treated patients achieved symptomatic remission by week 2 in ELEVATE UC 52 (15.3% vs 8.9%; P =0.049) and week 4 in ELEVATE UC 12 (27.5% vs 16.1%; P =0.007). Symptomatic remission increased in etrasimod- vs PBO-treated patients at each time point through week 12 in both ELEVATE UC 52 (46.0% vs 21.5%; P <0.001) and ELEVATE UC 12 (46.8% vs 29.5%; P =0.001) and was maintained through week 52 in ELEVATE UC 52 (43.4% vs 18.5%; P <0.001) (Figure 1A). Achievement of symptomatic response (Figure 1B), and significant improvements in RB and SF subscores, began as early as week 2 or week 4 for etrasimod vs PBO in ELEVATE UC 12 and ELEVATE UC 52, respectively. A significant difference in complete symptomatic remission was achieved at week 4 in both studies (Figure 1C). Subgroup analyses of symptomatic remission suggested a trend towards greater benefit in patients who were bio/JAKi naïve and patients with 1 prior bio/JAKi (vs >1) (Figures 2A-C). Conclusion: In this analysis, symptomatic relief was achieved by a greater proportion of patients treated with etrasimod vs PBO as early as week 2 and was sustained through week 52. At week 2, symptomatic response and improvements in RB and SF subscores were observed. The greatest benefits were seen in patients who had no prior exposure to bio/JAKi or 1 prior bio/JAKi therapy.